If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + -4x = 13 + -7x Solving -14 + -4x = 13 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -14 + -4x + 7x = 13 + -7x + 7x Combine like terms: -4x + 7x = 3x -14 + 3x = 13 + -7x + 7x Combine like terms: -7x + 7x = 0 -14 + 3x = 13 + 0 -14 + 3x = 13 Add '14' to each side of the equation. -14 + 14 + 3x = 13 + 14 Combine like terms: -14 + 14 = 0 0 + 3x = 13 + 14 3x = 13 + 14 Combine like terms: 13 + 14 = 27 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| 4a^2-9b^2=0 | | 4m^2-9k^2=0 | | 11n-14= | | 2x-6=8x-24 | | x+7(4)=16 | | 12k+9=0 | | 9+6r-4=9r+14-2r | | m^4-4m^3+7m^2-4m+6=0 | | m^7+m^5= | | 6(6v+6)=1+6v | | 12-8x=39-15x | | 2t+11t=104 | | 6x+7=-199-8x | | 14=20-2x | | 30k+10=18k+22 | | 49*7= | | 9d+18=2d+18 | | 2t=-16 | | 18+6m=12m+48 | | 12*6.8= | | 15y+60=30y+120 | | 2.1*6= | | 15y+40=30y+120 | | 18x-30=21x-14 | | 40-8h=4h-8 | | 5X(x+9)=6x+54 | | 24x+5=100 | | 9q-18=3q-36 | | -(-z-12)= | | 5x+1=3x-4 | | 6d-48=42-3d | | 11p-66=5p |